A guide to hazard identification methods. - Crawley, Frank (Elsevier, 2020)
A Guide to Hazard Identification Methods, Second Edition provides a description and examples of the most common techniques leading to a safer and more reliable chemical process industry. This new edition revises previous sections with up-to-date, linked sources. Furthermore, new elements include a more detailed account of purpose, Black Swan events, human factors, auditing and QA, more examples and a discussion of major incidents, HAZID and task analysis.
Description based upon print version of record.
Keywords: Chemical engineering -- Safety measures.; elektronické knihy; electronic books